Relation of Left Ventricular Diastolic Dysfunction to Serum Ferritin in Thalassemia Major - Faeq Salih, Aso; M. Hamawandi, Adnan (Kurdistan Journal of Applied Research, 2019)
A prospective study was conducted on 60 thalassemia major patients (33 males and 27 females ) in whom the LV function and its parameters where assessed by echocardiography in relation to serum ferritin during the period from 2nd October 2007 to 2nd February 2008, in Sulaimani pediatric teaching hospital. Patient and method: The age ranges of patients were ranged between 3 – 18 years old. The diastolic function of LV was assessed by (M-mode, D-mode, and pulse dopplar study of mitral and pulmonary vein) done. Among 60 patients seen, 25% shows normal LV diastolic function, the rest is 13% relaxation dysfunction, 27% shows Psuedonormal diastolic dysfunction and 35% shows restrictive pattern of LV diastolic dysfunction. Mean serum ferritin in normal and abnormal diastolic LV dysfunction was not so different. In addition nearly all LV parameters as ( LVEDD , LVESD , LA diameter , aortic root diameter , IVC , E ,A ,E/A ratio , A-E time , DT time , S,D,R waves ) where non significantly related to serum ferritin level , this means that P value is less than 0.05 . This means that the level of serum ferritin has no relation with the above parameters in which 75% of those parameters were already abnormal in comparison to the age of the child. Another finding shows that 25% of normal diastolic function is seen in serum levels above 1500 ng/l, in addition, 50% of diastolic dysfunction will associate serum ferritin of less than 500ng/l . P value is more than 0,05 this means that its non-significant. In conclusion, there is a non-significant correlation between serum ferritin and LV diastolic function, so serum ferritin is not a dependant indicator for myocardial iron deposition.